2022
DOI: 10.1126/science.abl4649
|View full text |Cite
|
Sign up to set email alerts
|

The biodiversity and ecosystem service contributions and trade-offs of forest restoration approaches

Abstract: Forest restoration is being scaled-up globally to deliver critical ecosystem services and biodiversity benefits, yet we lack rigorous comparison of co-benefit delivery across different restoration approaches. In a global synthesis, we use 25,950 matched data pairs from 264 studies in 53 countries to assess how delivery of climate, soil, water, and wood production services as well as biodiversity compares across a range of tree plantations and native forests. Carbon storage, water provisioning, and especially s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
171
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(184 citation statements)
references
References 415 publications
6
171
1
6
Order By: Relevance
“…Forest plantations are an important means of restoring degraded land, supplying ecosystem services, and mitigating climate change ( 1 4 ). In recent years, several global initiatives, such as the Bonn Challenge ( 5 ), the New York Declaration on Forests ( 6 ), and the United Nations (UN) Decade on Ecosystem Restoration ( 7 ), have been launched to restore degraded ecosystems and provide nature-based solutions to mitigate climate change by increasing global forest cover in the coming decades.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Forest plantations are an important means of restoring degraded land, supplying ecosystem services, and mitigating climate change ( 1 4 ). In recent years, several global initiatives, such as the Bonn Challenge ( 5 ), the New York Declaration on Forests ( 6 ), and the United Nations (UN) Decade on Ecosystem Restoration ( 7 ), have been launched to restore degraded ecosystems and provide nature-based solutions to mitigate climate change by increasing global forest cover in the coming decades.…”
mentioning
confidence: 99%
“…Foresters often prefer monoculture plantations because of their lower planting and management costs, targeted special uses of trees (e.g., kind and amount of timber production and economic value) ( 35 ), and the difficulty in identifying the site characteristics that will give the best result for a given multispecies plantation ( 30 , 35 ). However, a growing body of research is revealing the benefits of multispecies plantations in terms of productivity (this study), stability ( 16 , 36 ), community structure ( 15 ), and biodiversity ( 4 ). Therefore, we advocate a multifunctional cost-benefit analysis framework to identify planting strategies that optimize the benefits of forest plantations for restoration, conservation, and climate change mitigation.…”
mentioning
confidence: 99%
“…Reforestation is being carried out in a large scale in many countries. Recent studies across a range of tree plantations and native forests in 53 countries have revealed that carbon storage, soil erosion control, water conservation and biodiversity benefits are delivered better from native forests compared to monoculture tree plantations, although the latter yielded more wood (Hua et al 2022 ). This has to be kept in mind in reforestation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…On the time scales when both atmosphere and soil moisture are steady-state, runoff equals moisture convergence. When soil moisture S (mm) is not steady, then C = P − E = R + dS/dt, whereby R + dS/dt is referred to as the water yield (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…( 4). The blue triangle and square indicate, respectively, estimated dC/dP and measured dR/dP on the Loess Plateau in 1999-2015 according to Zhang et al (2022).…”
Section: Introductionmentioning
confidence: 99%